Analisi Yuridis Akad Perjanjian Jual Beli Perumahan - Pane, Abdul Hadi; Ahmatnijar, Ahmatnijar (Jurnal El-Thawalib, 2021)
Population growth that is increasingly dense, especially in Indonesia, causes a large community need for a decent settlement. Because housing is a necessity that is very necessary for humans. This is what makes business actors take advantage of housing sales and purchase agreements that are detrimental to consumers whose economy is low and are pressed for housing needs that are livable. So it is feared that it can harm one of the parties who should run in harmony considering that the relationship between the two is a symbiotic mutualism. The problem in this research is the practice of the sale and purchase agreement of cash housing and credit PT. Nato Jaya Group Purwodadi Village, Padangsidimpuan District Batunadua and juridical analysis of the sale and purchase agreement that has been promised by PT. Nato Jaya Group, Purwodadi Village, Padangsidimpuan District, Batunadua.This type of research is field research, where researchers go directly to the field to examine a problem. Sources of data used are primary data and secondary data. Methods of data collection using direct observation, interviews, and documentation.The results of this study and the discussion explain the rights and obligations of the parties in the house sale and purchase agreement are reciprocal. This means that the obligation of the developer (PT. Nato Jaya Group) is the right of the home buyer/consumer. Likewise, the consumer's obligations become the rights of the developer. The developer's obligations include submitting ownership rights to the houses being traded. The obligation to surrender ownership rights includes all actions that are legally required to transfer ownership rights to the house being traded from the seller to the buyer. while the obligation of the buyer/consumer of the house unit is to pay the purchase price at the time and place as determined according to the agreement.